Pemetaan Informasi Sebaran Bidang Ilmu pada Disertasi Mahasiswa Sekolah Pascasarjana IPB University Tahun 2016-2020 - Widiyati Kania; Himawan Deden (Perpustakaan IPB, 2022)
Introduction. The contribution of Universities in an effort to support the improvement of knowledge cannot be separated from various research results. Each Doctoral Program student conducts research and then compiles a report in the form of a dissertation with a topic tailored to his specialization. To find out the distribution of the topic of interest in the preparation of a scientific dissertation, a study was conducted. Research Methods. This research method uses quantitative methods with a descriptive approach. The data studied are all from IPB University Dissertation graduates in 2016 – 2020 as many as 859 dissertation titles. The data were analyzed after being grouped by field of science with UDC standards and then analyzed descriptively and mapped using VOSviewer software. Results and Discussion. The results of the study show that the number of dissertations for 2016 - 2020 is 859 titles from 28 departments. The field of science most researched is Natural Resources Management 90 titles. In 2019, the most dissertations produced were 251 titles. Visualization of VOSviewer on a co-word Map of 2685 keywords with a limit of at least 3 occurrences, resulting in 256 items divided into 18 clusters, 821 links and 1117 Total link Strength. Conclusion. The overall research results are divided into 43 fields of science based on the Universal Decimal Classification group. The largest group of fields of science is Natural Resources Management with 93 research titles, the 2nd most communication 51 research titles, the third most is the field of Fisheries science with 43 research titles.